Compound Odontoma in the Anterior Mandible: Diagnostic Challenges and Surgical Management of a Rare Presentation - Vikram Karande; Sanjay Ranade (Oral Sphere Journal of Dental and Health Sciences, 2025)
Background: Odontomas are the most common odontogenic tumours and are usually detected during the first two decades of life. They are considered hamartomas rather than true neoplasms and are broadly classified into compound and complex types. Compound odontomas commonly occur in the anterior maxilla and are often associated with delayed eruption or impaction of teeth. In contrast, osteomas are benign osteogenic lesions that differ from odontomas in their histogenesis and clinical behaviour. The occurrence of compound odontomas in the anterior mandible is uncommon. Case presentation: A 27-year-old female presented with delayed eruption of tooth 33 and displacement of adjacent teeth. Clinical examination revealed a hard swelling in the left anterior mandible. Cone-beam computed tomography (CBCT) revealed multiple radiopaque structures consistent with a compound odontoma. Tooth 32 was found to be impacted near the lesion. Surgical excision of the odontoma and extraction of the affected tooth were performed under local anaesthesia. Histopathological analysis confirmed the diagnosis of a compound odontoma, excluding the possibilities of odontoameloblastoma and ameloblastic fibroodontoma. Conclusion: This case was notable for the unusual anterior mandibular location of the compound odontoma, deviating from the typical anterior maxillary presentation. There was no history of trauma, infection, or familial predisposition. CBCT played a crucial role in defining the extent of the lesion and its relationship with adjacent structures. Early detection and surgical management facilitated future orthodontic planning for tooth 33. This case highlights the importance of considering compound odontoma in atypical locations when evaluating eruption disturbances. Accurate diagnosis relies on advanced imaging and histopathological confirmation. Prompt intervention prevents developmental complications and supports favourable outcomes.